VALIDATED MODIFIED LYCOPODIUM SPORE METHOD DEVELOPMENT FOR STANDARDISATION OF INGREDIENTS OF AN AYURVEDIC POWDERED FORMULATION-SHATAVARYADI CHURNA - Kumar, Puspendra; Jha, Shivesh; Naved, Tanveer (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Validated modified lycopodium spore method has been developed for simple and rapid quantification of herbal powdered drugs. Lycopodium spore method was performed on ingredients of Shatavaryadi churna, an ayurvedic formulation used as immunomodulator, galactagogue, aphrodisiac and rejuvenator. Estimation of diagnostic characters of each ingredient of Shatavaryadi churna individually was carried out. Microscopic determination, counting of identifying number, measurement of area, length and breadth of identifying characters were performed using Leica DMLS-2 microscope. The method was validated for intraday precision, linearity, specificity, repeatability, accuracy and system suitability, respectively. The method is simple, precise, sensitive, and accurate, and can be used for routine standardisation of raw materials of herbal drugs. This method gives the ratio of individual ingredients in the powdered drug so that any adulteration of genuine drug with its adulterant can be found out. The method shows very good linearity value between 0.988-0.999 for number of identifying character and area of identifying character. Percentage purity of the sample drug can be determined by using the linear equation of standard genuine drug.